High-entropy alloy brazing filler metal for dissimilar brazing connection of high-temperature alloy and carbon material and preparation method and application of high-entropy alloy brazing filler metal

By using the Ticocrfeni high -entropy alloy ingredients of non -equal atomic ratio, and controlling the diffusion of the element during the welding process, it solves the problem of the existing ingredients when connecting with carbon materials at high temperatures. Mechanical performance and high temperature stability.

CN119368970AActive Publication Date: 2025-01-28DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411272115.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-28
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

When existing solder materials are connected to carbon materials at high temperatures, they are prone to brittle carbides, resulting in insufficient mechanical properties and high-temperature service performance of the joints, limiting the application of carbon materials.

Method used

Ticocrfeni high -entropy alloys with non -equal atomic ratio are used to prepare high -entropy alloy material materials through high -energy ball mills and wet mills, and control the mutual diffusion of the parent material and the elements of the raw material during the welding process to inhibit the thickness of the interface reaction layer.

Benefits of technology

It significantly improves the mechanical properties and high temperature stability of the welding tank, reduces the generation of crispy carbides, enhances the intensity of the interface binding, and meets the high -strength reliability of high -temperature alloy and carbon material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368970A_ABST
    Figure CN119368970A_ABST
Patent Text Reader

Abstract

The invention discloses high-entropy alloy brazing filler metal for dissimilar brazing connection of a high-temperature alloy and a carbon material and a preparation method and application of the high-entropy alloy brazing filler metal. The high-entropy alloy brazing filler metal is composed of Ti, Co, Cr, Fe and Ni. The atomic percent ratio of Ti to Co to Cr to Fe to Ni is (0.6 to 0.65): (0.9 to 1.1): (0.9 to 1.1): (0.9 to 1.1): (2.0 to 2.1). The non-equal-atomic-ratio TiCoCrFeNi high-entropy alloy brazing filler metal is eutectic high-entropy alloy brazing filler metal with plasticity and strength and excellent performance, after the non-equal-atomic-ratio TiCoCrFeNi high-entropy alloy brazing filler metal is adopted for brazing, a part of high-entropy solid solution phase can be reserved in the center position of a brazing joint through metallurgical reaction and element diffusion at the high temperature, generation of brittle carbide in the joint is inhibited through high mixed entropy, and the high-entropy alloy brazing filler metal can be used for brazing. The mechanical property of the joint is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of brazing technology, and more specifically, to a high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material, and a preparation method and application thereof. Background Art

[0002] Carbon materials such as graphite and C / C composites have many desirable properties, such as high temperature stability, high resistance to thermal ablation, excellent thermal conductivity and good mechanical properties. Therefore, they have attracted widespread attention as lightweight thermal structural materials in the aerospace field, such as rocket engines and solid rocket nozzles. However, C / C composites are characterized by high brittleness and poor machinability, which means that they are difficult to manufacture into complex C / C structural parts. This type of high-temperature carbon material usually needs to be combined with itself or other materials to form composite components for industrial applications. Therefore, high-temperature resistant, high-strength and tough joints are the key to expanding the application range of C / C composites.

[0003] Active metal brazing is currently the most commonly used method for connecting carbon materials. It has a simple process and can obtain reliable joints in a relatively short time. Currently, traditional brazing materials such as Ti-based and Ag-based brazing materials are mostly used for brazing carbon materials. However, the active metal elements Ti, Cr, etc. contained in traditional brazing materials are prone to generate a large amount of brittle carbides at the interface and inside the joint, which greatly weakens the mechanical properties of the joint, especially the high-temperature service performance, and severely limits the application of carbon materials. Therefore, in view of the problem of poor joint bonding performance of existing brazing materials, it is urgent to develop new alloy brazing materials to achieve high-strength and reliable connection of carbon materials.

[0004] A high entropy alloy is an alloy composed of five or more elements with a content of approximately 5 at.% to 35 at.%. Unlike traditional alloys that easily form intermetallic compounds, high entropy alloys have random distribution of atoms and chemical components in the alloy due to the high mixing entropy effect, which promotes the formation of simple single-phase solid solutions and produces strong solid solution strengthening, thereby enhancing the resistance to deformation and fracture. The hysteresis diffusion effect makes the diffusion of atoms in the alloy extremely difficult, which can inhibit the formation of brittle phases at the ceramic-metal interface during brazing, while reducing deformation and residual stress in the joint, and can significantly improve the strength, hardness and other mechanical properties of the alloy, thereby improving the performance of the joint. The lattice distortion effect affects the mechanical properties of the alloy by adjusting the lattice structure and changing the dislocation density and grain boundary energy of the alloy. Severe lattice distortion can lead to local strengthening of the alloy, which has a stronger ability to resist dislocations than traditional alloys, improves the hardness and deformation resistance of the alloy, and is very beneficial to the improvement of the mechanical properties of the joint. The "cocktail" effect increases the complexity and diversity of the joint, improves the stability and deformation resistance of the material, thereby ensuring the long-term stability and reliability of the joint, thereby expanding the scope and application value of the brazed joint. Therefore, the "cocktail" effect of high entropy alloys provides a higher performance material selection and application guarantee for interface connection. During the solidification process, the disordered atoms of various elements diffuse slowly over long distances, the nucleation and growth of the solute redistribution process are delayed, and nanophases are easily formed. Some high entropy alloys also have a tendency to become amorphous, and have high strength and toughness, low melting point effect and a narrow solid-liquid phase range. These characteristics make it possible for high entropy alloys to be used as solders.

[0005] Fu et al. used the eutectic high entropy alloy Nb0.74CoCrFeNi2 as brazing material. Although they successfully brazed the C / C composite material, due to the good reactivity of Nb and Cr elements with the carbon phase, a brittle Nb(s,s) layer was generated on the C / C parent material side and the brittle layer thickened with increasing temperature. When the connection temperature was 1260°C, the shear strength of the joint only reached 32.3MPa, and the fracture mainly occurred at the interface, showing a brittle fracture mode. However, the existing process methods have not fundamentally improved the brittleness of the interface metal compound. Therefore, how to effectively reduce the intrinsic brittleness of the interface metal compound is a key issue to be solved in order to improve the strength and reliability of the brazed joint and obtain a brazed joint that meets the requirements of practical applications. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art, and to provide a high entropy alloy brazing material for dissimilar brazing connection between high-temperature alloy and carbon material, and its preparation method and application. The non-equiatomic ratio TiCoCrFeNi high entropy alloy brazing material proposed in the present invention is a eutectic high entropy alloy brazing material with excellent performance that takes into account both plasticity and strength. After brazing, after metallurgical reaction and element diffusion at high temperature, part of the high entropy solid solution phase will be retained in the center of the brazed joint. The high mixing entropy inhibits the formation of brittle carbides in the joint, and significantly improves the mechanical properties of the joint. The present invention can effectively control the mutual diffusion of the base material and the brazing material elements during the brazing connection process by means of the hysteresis diffusion effect of the high entropy alloy, thereby inhibiting the thickness of the interface reaction layer and improving the bonding strength.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material. The high entropy alloy brazing filler metal is composed of Ti, Co, Cr, Fe and Ni; the atomic percentages of Ti, Co, Cr, Fe and Ni are (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1).

[0009] The present invention also discloses a method for preparing the high entropy alloy brazing filler metal for dissimilar brazing connection between a high temperature alloy and a carbon material as described above, comprising the following steps:

[0010] Mix Ti, Co, Cr, Fe and Ni in atomic percentages of (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1) to obtain a metal raw material;

[0011] The metal raw material is subjected to high-energy ball milling by a mechanical alloying method to obtain the high-entropy alloy brazing material.

[0012] The present invention also discloses a brazing method using the high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material as described above, or the high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material prepared by the above preparation method, comprising the following steps:

[0013] (1) Grinding and cleaning the base material to be welded using SiC sandpaper to obtain a pretreated base material;

[0014] (2) mixing the high entropy alloy powder and anhydrous ethanol to obtain a paste solder;

[0015] (3) coating the paste solder on the surface of the pretreated base material to form a welding assembly with a sandwich structure of carbon material / solder intermediate layer / high-temperature alloy in sequence;

[0016] (4) placing the welded assembly into a graphite mold and applying a pressure of 0.5 MPa to 5 MPa, heating the assembly to 1150°C to 1200°C in a vacuum furnace at a heating rate of 15°C / min to 20°C / min, keeping the temperature for 10 min to 20 min, then heating the assembly to the brazing temperature at a heating rate of 5°C / min to 10°C / min, keeping the temperature for 10 min to 30 min, cooling the assembly to 400°C to 600°C at a rate of 5°C / min to 10°C / min, and cooling the assembly to room temperature in the furnace to complete the brazing.

[0017] Implementing the embodiments of the present invention will have the following beneficial effects:

[0018] (1) The non-equiatomic ratio TiCoCrFeNi high entropy alloy brazing filler metal proposed in the present invention has a high mixing entropy. The Ti element and other metal elements have a relatively negative binary mixing enthalpy. Therefore, in the alloy structure, in addition to the FCC phase with good plasticity, there is also an IMC second phase with excellent high-temperature performance. Compared with a single solid solution phase high entropy alloy, this is a eutectic high entropy alloy brazing filler metal with excellent performance that takes into account both plasticity and strength. After brazing is completed, after metallurgical reaction and element diffusion at high temperature, part of the high entropy solid solution phase will be retained in the center of the brazed joint. The high mixing entropy inhibits the formation of brittle carbides in the joint, significantly improving the mechanical properties of the joint.

[0019] (2) The present invention utilizes the hysteresis diffusion effect of high entropy alloy to effectively control the mutual diffusion of base material and brazing filler metal elements during the brazing connection process, thereby suppressing the thickness of the interface reaction layer and improving the bonding strength.

[0020] (3) The high entropy alloy brazing material disclosed in the present invention contains high content of solid solution strengthening elements such as Co and Cr, which are common in nickel-based high temperature alloys. These elements are similar to the Ni crystal structure and are easy to form a solid solution phase. At the same time, the high content of Ni makes the high entropy brazing material have good compatibility with the nickel-based high temperature alloy.

[0021] (4) Adding an appropriate amount of Ti as an active element to the high entropy alloy brazing filler metal disclosed in the present invention can significantly improve the wettability of the brazing filler metal on the surface of the matrix carbon material. At the brazing temperature, the molten alloy brazing filler metal penetrates into the pores of the matrix under the action of capillary force and reactive wetting, forming a mechanical locking structure, which can significantly improve the interface bonding strength.

[0022] (5) The high entropy alloy brazing filler metal disclosed in the present invention combines the high entropy alloy theory and the design method of eutectic high entropy alloy to obtain a reasonable Ti-Co-Cr-Fe-Ni component ratio, which can ensure one-time welding without defects such as dissolution, lack of fusion, and microcracks inside the weld.

[0023] (6) The high entropy alloy solder disclosed in the present invention mainly comprises an FCC phase, has good plasticity, can be processed into a variety of different solder forms such as powder and block, and can be used for solder assembly under different weldment shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of base material, solder size and assembly.

[0025] Figure 2 This is the thermal cycle curve of the brazing process.

[0026] Figure 3 This is the interface microstructure diagram of graphite / TiCoCrFeNi / GH4169 brazed joint.

[0027] Figure 4 This is a macroscopic picture of the C / C-GH4169 connector.

[0028] Figure 5 This is a macroscopic image of the C / SiC-GH4169 connector. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0030] The invention discloses a high-entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material. The high-entropy alloy brazing filler metal consists of Ti, Co, Cr, Fe and Ni; the atomic percentages of Ti, Co, Cr, Fe and Ni are (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1).

[0031] In one specific embodiment, the atomic percentage of Ti, Co, Cr, Fe and Ni is 0.63:1:1:1:2.1.

[0032] In a specific embodiment, Ti, Co, Cr, Fe and Ni are pure metal powders with a purity of ≥99.5%;

[0033] In a specific embodiment, the particle size of the pure metal powder is 260 mesh to 390 mesh;

[0034] The present invention also discloses a method for preparing a high entropy alloy brazing filler metal for dissimilar brazing connection between a high temperature alloy and a carbon material as in any embodiment of the present invention, comprising the following steps:

[0035] S1. Mix Ti, Co, Cr, Fe and Ni according to the atomic percentage of (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1) to obtain a metal raw material.

[0036] S2. The metal raw materials are subjected to high-energy ball milling by mechanical alloying method to obtain high-entropy alloy brazing material.

[0037] In a specific embodiment, high-energy ball milling is to use a planetary ball mill to mechanically alloy the metal raw material in two stages, which specifically includes the following steps:

[0038] (1) In a protective gas, the metal raw material is subjected to high-energy ball milling by a mechanical alloying method to obtain a dry-milled product.

[0039] (2) Adding liquid medium to the dry-grinding product for wet grinding, and vacuum drying to obtain a high-entropy alloy solder.

[0040] In a specific embodiment, in step (1), the ball-to-material ratio is (10-15):1; the ball milling speed is 300 r / min-400 r / min; the ball milling time is 36 h-48 h; and the protective gas is high-purity argon.

[0041] In a specific embodiment, in step (2), the liquid medium is alcohol; the mass ratio of the liquid medium to the dry-milled product is 1 to 1.5:1, and the ball milling time is 10 h to 20 h.

[0042] In a specific embodiment, the preparation method further comprises: vacuum drying the wet-milled product at 30° C. to 40° C. for 12 hours.

[0043] In a specific embodiment, the grinding balls used in the high energy ball mill include grinding balls with a diameter of 8mm-10mm and grinding balls with a diameter of 5mm-6mm; the mass ratio of the grinding balls with a diameter of 8mm-10mm and the grinding balls with a diameter of 5mm-6mm is 3.5:6.5.

[0044] In a specific embodiment, the ball mill jar and the grinding balls are made of stainless steel.

[0045] The present invention also discloses a brazing method using a high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material as in any embodiment, or a high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material prepared by a preparation method as in any embodiment, comprising the following steps:

[0046] (1) The base material to be welded is polished and cleaned using SiC sandpaper to obtain a pretreated base material.

[0047] In a specific embodiment, step (1) specifically includes: polishing the surface of the parent material to be welded using SiC sandpaper of 120 mesh, 300 mesh, 600 mesh, 1200 mesh and 1500 mesh in sequence to remove surface cutting scratches, oxide film, burrs and other various defects, and placing the polished parent material to be welded in anhydrous ethanol for ultrasonic oscillation cleaning for 5 minutes to 15 minutes to remove surface grease and stains.

[0048] (2) High entropy alloy powder and anhydrous ethanol are mixed to obtain a paste-like solder.

[0049] (3) Applying a paste-like solder to the surface of the pretreated base material to form a welding assembly having a sandwich structure of carbon material / solder intermediate layer / high-temperature alloy.

[0050] (4) Place the welded assembly in a graphite mold and apply a pressure of 0.5 MPa to 5 MPa. Heat the assembly to 1150 to 1200 °C in a vacuum furnace at a heating rate of 15 °C / min to 20 °C / min, keep the temperature for 10 to 20 min, then heat the assembly to the brazing temperature at a heating rate of 5 to 10 °C / min. Keep the temperature for 10 to 30 min, then cool the assembly to 400 to 600 °C at a rate of 5 to 10 °C / min. Cool the assembly to room temperature in the furnace to complete the brazing.

[0051] In a specific embodiment, in step (3), the thickness of the solder intermediate layer is 0.2 mm to 0.4 mm.

[0052] In one specific embodiment, in step (4), the vacuum degree in the vacuum furnace is maintained at less than 5×10 -3 Pa.

[0053] The following are specific embodiments

[0054] In the present embodiment, pure metal powder is used as raw material, the ingredients are prepared according to the corresponding component ratio, and the high entropy alloy powder is prepared by ball milling using a mechanical alloying method. After the brazing alloy powder with qualified components is prepared, it is used for high-temperature brazing connection of carbon materials.

[0055] Example 1

[0056] The preparation method of the high entropy alloy solder of this embodiment is carried out according to the following steps:

[0057] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.63:1:1:1:2.1, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0058] Step 2: Prepare high entropy solder by mechanical alloying method. The raw materials weighed in step 1 were subjected to high-energy ball milling in a stainless steel ball mill for 48 h, and then wet milled for 10 h with anhydrous ethanol, the ball milling speed was 350 r / min, the ball-to-material ratio was 10:1, and argon was filled in the ball mill as a protective gas during the ball milling process.

[0059] Step 3: Place the ball mill after wet grinding in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain high entropy solder powder.

[0060] Use high entropy solder powder to braze graphite and GH4169 high-temperature alloy: Grind the surfaces of graphite and GH4169 high-temperature alloy to be welded with fine sandpaper to remove surface oil and defects, then put the graphite and GH4169 high-temperature alloy into anhydrous ethanol and ultrasonically clean them for 5 minutes. Weigh a small amount of high-entropy alloy powder, add an appropriate amount of anhydrous ethanol as a solvent, and prepare the solder slurry by ultrasonic oscillation. Apply the slurry evenly on the surface of the high-temperature alloy with a thickness of about 0.2 mm. After the slurry is dry, assemble it from top to bottom in the form of graphite / high-entropy solder middle layer / GH4169 high-temperature alloy. After the assembly is completed, the sample is as follows Figure 1 As shown, a pressure of 0.5 to 5 MPa is applied to ensure close contact between the parts during the connection process. The sample is then placed in a vacuum furnace, first heated to 1150°C at a heating rate of 15°C / min and kept warm for 10 minutes to ensure that the temperature of each part of the connection is consistent. Then the temperature is raised to the target temperature at a rate of 15°C / min and kept warm at this temperature for 10-20 minutes. After the insulation is completed, the temperature is lowered to 450°C at a rate of 5°C / min, and then cooled to room temperature with the furnace to complete the brazing connection between graphite and GH4169 high-temperature alloy. The heating curve is shown in Figure 2 The vacuum furnace is kept in vacuum (vacuum degree < 5×10 -3 Pa).

[0061] The microstructure and element distribution of the graphite / TiCoCrFeNi / GH4169 high temperature alloy brazed joint obtained in this example are as follows: Figure 3 As shown in the figure. It can be seen from the figure that the high entropy alloy is well connected with graphite and high temperature alloy, and the interface layer is uniform and continuous. The results of energy spectrum analysis show that the Cr element is mainly concentrated on the interface on the graphite side, and it reacts with C in the graphite matrix to form an interface layer, indicating that the high entropy alloy has good reactivity with the carbon material matrix. There is a small amount of Ti element aggregation near the interface layer, and the content of Ni, Fe and Co elements in the unreacted high entropy alloy layer is high and evenly distributed, which is caused by the different carbide formation energies of different elements.

[0062] Example 2

[0063] The only difference between this embodiment and embodiment 1 is that the base material used is a C / C composite material.

[0064] Figure 4 The macroscopic photo of the connection after the connection is completed. Overall, at the brazing temperature, the high entropy alloy wets well on the surface of the C / C composite material, and the high-temperature alloy does not dissolve or deform.

[0065] Example 3

[0066] The only difference between this embodiment and embodiment 1 is that the base material used is a C / SiC composite material.

[0067] Figure 5 The macroscopic photo of the connection after the connection is completed. Overall, at the brazing temperature, the high entropy alloy wets well on the surface of the C / SiC composite material, and the high-temperature alloy does not dissolve or deform.

[0068] Example 4

[0069] The only difference between this embodiment and Embodiment 1 is that pure metal powder raw material is weighed according to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.65:1:1:1:2.1.

[0070] The preparation method of the high entropy alloy solder of this embodiment is carried out according to the following steps:

[0071] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.65:1:1:1:2.1, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0072] Step 2: Prepare high entropy solder by mechanical alloying method. The raw materials weighed in step 1 were subjected to high-energy ball milling in a stainless steel ball mill for 48 h, and then wet milled for 10 h with anhydrous ethanol, the ball milling speed was 350 r / min, the ball-to-material ratio was 10:1, and argon was filled in the ball mill as a protective gas during the ball milling process.

[0073] Step 3: Place the ball mill after wet grinding in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain high entropy solder powder.

[0074] Brazing graphite and GH4169 superalloy using high entropy solder powder: The surfaces of graphite and GH4169 superalloy to be welded are polished with fine sandpaper to remove surface oil and defects, and then the graphite and GH4169 superalloy are placed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Weigh a small amount of high entropy alloy powder, add an appropriate amount of anhydrous ethanol as a solvent, and prepare the solder slurry by ultrasonic oscillation. The slurry is evenly coated on the surface of the superalloy with a thickness of about 0.2mm. After the slurry is dried, it is assembled in the form of graphite / high entropy solder intermediate layer / GH4169 superalloy from top to bottom, and a pressure of 0.5 to 5MPa is applied to make the parts in close contact during the connection process. The sample is then placed in a vacuum furnace, first heated to 1150℃ at a heating rate of 15℃ / min and kept warm for 10min to ensure that the temperature of each part of the connection is consistent. Then the temperature is raised to the target temperature at a rate of 15℃ / min and kept warm at this temperature for 10-20min. After the insulation is completed, the temperature is lowered to 450℃ at a rate of 5℃ / min, and then cooled to room temperature with the furnace to complete the brazing connection between graphite and GH4169 high-temperature alloy. The vacuum furnace is kept in vacuum (vacuum degree < 5×10 - 3 Pa).

[0075] In the graphite / TiCoCrFeNi / GH4169 high temperature alloy brazing joint obtained in this embodiment, the melting point of the brazing material is slightly increased, the fluidity of the liquid brazing material is deteriorated, the interface reaction layer is thinned, and obvious cracks or holes exist inside the weld.

[0076] Example 5

[0077] The only difference between this embodiment and Embodiment 1 is that pure metal powder raw material is weighed according to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.6:0.9:0.9:0.9:2.

[0078] The preparation method of the high entropy alloy solder of this embodiment is carried out according to the following steps:

[0079] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.6:0.9:0.9:0.9:2, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0080] Step 2: Prepare high entropy solder by mechanical alloying method. The raw materials weighed in step 1 were subjected to high-energy ball milling in a stainless steel ball mill for 48 h, and then wet milled for 10 h with anhydrous ethanol, the ball milling speed was 350 r / min, the ball-to-material ratio was 10:1, and argon was filled in the ball mill as a protective gas during the ball milling process.

[0081] Step 3: Place the ball mill after wet grinding in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain high entropy solder powder.

[0082] Brazing graphite and GH4169 superalloy using high entropy solder powder: The surfaces of graphite and GH4169 superalloy to be welded are polished with fine sandpaper to remove surface oil and defects, and then the graphite and GH4169 superalloy are placed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Weigh a small amount of high entropy alloy powder, add an appropriate amount of anhydrous ethanol as a solvent, and prepare the solder slurry by ultrasonic oscillation. The slurry is evenly coated on the surface of the superalloy with a thickness of about 0.2mm. After the slurry is dried, it is assembled in the form of graphite / high entropy solder intermediate layer / GH4169 superalloy from top to bottom, and a pressure of 0.5 to 5MPa is applied to make the parts in close contact during the connection process. The sample is then placed in a vacuum furnace, first heated to 1150℃ at a heating rate of 15℃ / min and kept warm for 10min to ensure that the temperature of each part of the connection is consistent. Then the temperature is raised to the target temperature at a rate of 15℃ / min and kept warm at this temperature for 10-20min. After the insulation is completed, the temperature is lowered to 450℃ at a rate of 5℃ / min, and then cooled to room temperature with the furnace to complete the brazing connection between graphite and GH4169 high-temperature alloy. The vacuum furnace is kept in vacuum (vacuum degree < 5×10 - 3 Pa).

[0083] In the graphite / TiCoCrFeNi / GH4169 high temperature alloy brazed joint obtained in this embodiment, due to the low content of active metal elements in the brazing filler metal, the interface reaction is insufficient and the interface bonding strength is low.

[0084] Example 6

[0085] The only difference between this embodiment and Embodiment 1 is that pure metal powder raw material is weighed according to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.5:1:1:1:2.1.

[0086] The preparation method of the high entropy alloy solder of this embodiment is carried out according to the following steps:

[0087] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.5:1:1:1:2, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0088] Step 2: Prepare high entropy solder by mechanical alloying method. The raw materials weighed in step 1 were subjected to high-energy ball milling in a stainless steel ball mill for 48 h, and then wet milled for 10 h with anhydrous ethanol, the ball milling speed was 350 r / min, the ball-to-material ratio was 10:1, and argon was filled in the ball mill as a protective gas during the ball milling process.

[0089] Step 3: Place the ball mill after wet grinding in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain high entropy solder powder.

[0090] Brazing graphite and GH4169 superalloy using high entropy solder powder: The surfaces of graphite and GH4169 superalloy to be welded are polished with fine sandpaper to remove surface oil and defects, and then the graphite and GH4169 superalloy are placed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Weigh a small amount of high entropy alloy powder, add an appropriate amount of anhydrous ethanol as a solvent, and prepare the solder slurry by ultrasonic oscillation. The slurry is evenly coated on the surface of the superalloy with a thickness of about 0.2mm. After the slurry is dried, it is assembled in the form of graphite / high entropy solder intermediate layer / GH4169 superalloy from top to bottom, and a pressure of 0.5 to 5MPa is applied to make the parts in close contact during the connection process. The sample is then placed in a vacuum furnace, first heated to 1150℃ at a heating rate of 15℃ / min and kept warm for 10min to ensure that the temperature of each part of the connection is consistent. Then the temperature is raised to the target temperature at a rate of 15℃ / min and kept warm at this temperature for 10-20min. After the insulation is completed, the temperature is lowered to 450℃ at a rate of 5℃ / min, and then cooled to room temperature with the furnace to complete the brazing connection between graphite and GH4169 high-temperature alloy. The vacuum furnace is kept in vacuum (vacuum degree < 5×10 - 3 Pa).

[0091] The alloy obtained in this example fails to form a stable solid solution structure, and a large amount of brittle intermetallic compounds exist in the joint after the brazing connection is completed.

[0092] Comparative Example 1

[0093] Compared with Example 1, the only difference between this comparative example is that the high-energy ball milling step is replaced by ordinary ball milling, and the specific steps are as follows:

[0094] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.63:1:1:1:2.1, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0095] Step 2: Prepare the brazing material by mechanical alloying method. The raw materials weighed in step 1 were ball-milled in a stainless steel ball mill for 48 hours, and then wet-milled for 10 hours with anhydrous ethanol, the ball milling speed was 200 r / min, the ball-to-material ratio was 10:1, and argon was filled in the ball mill as the protective gas during the ball milling process.

[0096] Step 3: Place the ball mill after wet grinding in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain solder powder.

[0097] The alloy powder obtained by the ball milling process was found to be not completely alloyed through XRD analysis.

[0098] Comparative Example 2

[0099] The only difference between this comparative example and Example 1 is that this comparative example only adopts wet grinding. The specific steps are:

[0100] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.63:1:1:1:2.1, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0101] Step 2: Prepare the brazing material by mechanical alloying method. The raw materials weighed in step 1 are placed in a stainless steel ball mill, and anhydrous ethanol is added for ball milling for 48 hours, the ball milling speed is 350 r / min, the ball-to-material ratio is 10:1, and argon is filled in the ball mill as the protective gas during the ball milling process.

[0102] Step 3: Place the ball mill after ball milling in step 2 into a vacuum drying oven and vacuum dry for 12 hours to obtain solder powder.

[0103] The alloy powder obtained by the ball milling process was found to be not completely alloyed through XRD analysis.

[0104] Comparative Example 3

[0105] The only difference between this comparative example and Example 1 is that this comparative example only adopts dry grinding. The specific steps are:

[0106] Step 1: According to the composition ratio of high entropy alloy solder Ti:Co:Cr:Fe:Ni=0.63:1:1:1:2.1, weigh pure metal powder raw materials. The raw materials are all pure metal powders with a purity of 99.5%.

[0107] Step 2: Prepare the brazing material by mechanical alloying method. The raw materials weighed in step 1 are ball-milled in a stainless steel ball mill for 48 hours, with a ball-milling speed of 350 r / min and a ball-to-material ratio of 10:1. Argon is filled in the ball mill as a protective gas during the ball milling process.

[0108] After the ball milling process is completed, most of the alloy brazing filler metal is cold welded on the grinding balls and the inner wall of the tank. The average particle size of the alloy particles is about 30 to 40 μm, which is much larger than the powder particle size (about 5 μm) obtained by the dry grinding and wet grinding mixed process. XRD analysis of the alloy particles found that alloying was achieved. However, after welding, obvious cracks appeared in the weld due to the poor fluidity of the large-particle brazing filler metal.

[0109] Table 1 Shear strength of brazed joints of Examples 1-6 and Comparative Examples 1-3

[0110]

[0111] In summary, the present invention has rationally improved the composition and addition ratio of the high entropy alloy solder through multiple tests, and has regulated and optimized the preparation process. After brazing with the non-equiatomic ratio TiCoCrFeNi high entropy alloy solder of the present invention, part of the high entropy solid solution phase will be retained at the center of the brazed joint, and the high mixing entropy inhibits the formation of brittle carbides in the joint, significantly improving the mechanical properties of the joint. The present invention can effectively control the mutual diffusion of the base material and the solder elements during the brazing connection process by means of the hysteresis diffusion effect of the high entropy alloy, thereby inhibiting the thickness of the interface reaction layer and improving the bonding strength.

[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high entropy alloy brazing material for dissimilar brazing connection between high temperature alloy and carbon material, characterized in that: The high entropy alloy solder is composed of Ti, Co, Cr, Fe and Ni; the atomic percentages of Ti, Co, Cr, Fe and Ni are (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1).

2. The high entropy alloy brazing filler metal for dissimilar brazing connection between high temperature alloy and carbon material according to claim 1, characterized in that: The atomic percentage of Ti, Co, Cr, Fe and Ni is 0.63:1:1:1:2.

1.

3. The high entropy alloy brazing filler metal for dissimilar brazing connection between high temperature alloy and carbon material according to claim 1, characterized in that: The Ti, Co, Cr, Fe and Ni are pure metal powders with a purity of ≥99.5%; The particle size of the pure metal powder is 260 mesh to 390 mesh.

4. A method for preparing a high entropy alloy brazing filler metal for dissimilar brazing connection between a high temperature alloy and a carbon material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Mix Ti, Co, Cr, Fe and Ni in atomic percentages of (0.6-0.65):(0.9-1.1):(0.9-1.1):(0.9-1.1):(2.0-2.1) to obtain a metal raw material; The metal raw material is subjected to high-energy ball milling by a mechanical alloying method to obtain the high-entropy alloy brazing material.

5. The preparation method according to claim 4, characterized in that: The high-energy ball milling is to use a planetary ball mill to mechanically alloy the metal raw material in two stages, and specifically includes the following steps: (1) In a protective gas, the metal raw material is subjected to high-energy ball milling by a mechanical alloying method to obtain a dry-milled product; (2) adding a liquid medium to the dry-grinding product for wet grinding, and vacuum drying to obtain the high-entropy alloy solder.

6. The preparation method according to claim 5, characterized in that: In step (1), the ball-to-material ratio is (10-15):1; the ball milling speed is 300 r / min-400 r / min; the ball milling time is 36 h-48 h; the protective gas is high-purity argon; In step (2), the liquid medium is alcohol; the mass ratio of the liquid medium to the dry-milled product is 1 to 1.5:1, and the ball milling time is 10 h to 20 h.

7. The preparation method according to claim 4, characterized in that: The grinding balls used in the high-energy ball mill include grinding balls with a diameter of 8 mm to 10 mm and grinding balls with a diameter of 5 mm to 6 mm; The mass ratio of the grinding balls with a diameter of 8 mm to 10 mm to the grinding balls with a diameter of 5 mm to 6 mm is 3.5:6.5; The grinding balls are made of stainless steel.

8. A brazing method using the high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material as described in any one of claims 1 to 3, or the high entropy alloy brazing filler metal for dissimilar brazing connection between a high-temperature alloy and a carbon material prepared by the preparation method as described in any one of claims 4 to 7, characterized in that: The following steps are involved: (1) grinding and cleaning the base material to be welded using SiC sandpaper to obtain a pretreated base material; (2) mixing the high entropy alloy powder and anhydrous ethanol to obtain a paste solder; (3) coating the paste solder on the surface of the pretreated base material to form a welding assembly with a sandwich structure of carbon material / solder intermediate layer / high-temperature alloy in sequence; (4) placing the welded assembly into a graphite mold and applying a pressure of 0.5 MPa to 5 MPa, heating the assembly to 1150°C to 1200°C in a vacuum furnace at a heating rate of 15°C / min to 20°C / min, keeping the temperature for 10 min to 20 min, then heating the assembly to the brazing temperature at a heating rate of 5°C / min to 10°C / min, keeping the temperature for 10 min to 30 min, cooling the assembly to 400°C to 600°C at a rate of 5°C / min to 10°C / min, and cooling the assembly to room temperature in the furnace to complete the brazing.

9. The brazing method according to claim 8, characterized in that: In step (3), the thickness of the solder intermediate layer is 0.2 mm to 0.4 mm.

10. The brazing method according to claim 8, characterized in that: In step (4), the vacuum degree in the vacuum furnace is maintained at <5×10 -3 Pa.

Citation Information

Patent Citations

  • High-entropy brazing filler metal for brazing non-oxide ceramics and non-oxide ceramic composite material and preparation method of brazing filler metal

    CN102689109A

  • Eutectic high-entropy alloy brazing filler metal for brazing titanium and titanium alloy and stainless steel and preparation method of eutectic high-entropy alloy brazing filler metal

    CN113814604A

  • High-entropy brazing filler metal for brazing composite material and high-temperature alloy, preparation method of high-entropy brazing filler metal and method for brazing high-temperature alloy

    CN115229382A

  • Low-density FeCrNiAl series high-entropy alloy powder and preparation method thereof

    CN117626090A

  • Cobalt-based alloy, powder mixture, process and component

    DE102020203436A1

Cited By

  • Method for connecting SiGe high-temperature thermoelectric material and metal electrode

    CN120680078A

  • A method for connecting a SiGe high-temperature thermoelectric material and a metal electrode

    CN120680078B